Can someone die of a broken heart: cases of lethal myocardial infarctions with ventricular wall ruptures - Gómez-Piña, Juan José; Castro Luna, Vanessa; León Alfaro, Natalia; Medina Reyes, Abraham Gilberto; Domínguez Hernández, Edgar Ulises; Arias Velarde, Luis Fernando (International Journal of Research in Medical Sciences, 2025)
Ventricular septal rupture is a dreaded complication of transmural myocardial infarction, most often due to occlusion of the left anterior descending artery. The resulting interventricular shunt leads to acute heart failure and cardiogenic shock in the early days following infarction. We present three cases of patients admitted with myocardial infarction who developed ventricular septal defects within 48 hours of admission. All were diagnosed rapidly with echocardiography and underwent urgent surgical repair. However, each experienced persistent hemodynamic instability despite inotropes and intra-aortic balloon pump support. Early postoperative mortality occurred in all three patients, between 2 to 9 days after surgery. Although expedited diagnosis and surgical intervention temporarily stabilized these patients, the post-infarction septal rupture proved lethal in each case. Earlier revascularization or pre-emptive mechanical circulatory support may be needed to improve outcomes from this catastrophic mechanical complication of myocardial infarction.